2016
DOI: 10.1080/03075079.2015.1126817
|View full text |Cite
|
Sign up to set email alerts
|

Scale and scope economies of distance education in Australian universities

Abstract: Despite compelling qualitative arguments for scale and scope economies in university-level distance education, as distinct from traditional class-based face-to-face instruction, there is little rigorous quantitative evidence in support. In this paper, we explore the scale and scope economies of distance education using a multiplicatively separable cost function and a sample of 37 Australian public universities over the 10-year period from 2003 to 2012. The results suggest strong overall scale and scope economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…In a study by Li and Chen (2012) higher education institutions benefit the most from two of four outputs-research outputs and distance education-with teaching via distance education at both the undergraduate and graduate levels more profitable than F2F teaching at higher education institutions in China. Zhang and Worthington (2017) reported an increasing cost benefit for the use of distance education over F2F instruction as seen at 37 Australian public universities over 9 years from 2003 to 2012. Maloney et al (2015) and Kemp and Grieve (2014) also found significant savings in higher education when using online learning platforms vs. F2F learning.…”
Section: Discussion and Social Implicationsmentioning
confidence: 99%
“…In a study by Li and Chen (2012) higher education institutions benefit the most from two of four outputs-research outputs and distance education-with teaching via distance education at both the undergraduate and graduate levels more profitable than F2F teaching at higher education institutions in China. Zhang and Worthington (2017) reported an increasing cost benefit for the use of distance education over F2F instruction as seen at 37 Australian public universities over 9 years from 2003 to 2012. Maloney et al (2015) and Kemp and Grieve (2014) also found significant savings in higher education when using online learning platforms vs. F2F learning.…”
Section: Discussion and Social Implicationsmentioning
confidence: 99%
“…Представленная в предыдущем разделе публикация [14], скорее, подтверждает выводы о сочетании эффектов экономии и от разнообразия, и от масштаба в случае дистанционного обучения.…”
Section: полемика вокруг «экономики масштаба» и «экономики разнообразия» вузов в условиях цифровизации образованияunclassified
“…Moreover, “once the courses are prepared, the delivery costs of DE arise from the maintenance of large files and multiple simultaneous users and typically require considerable bandwidth. Together, these factors imply that distance‐education courses and programmes have a relatively high share of fixed costs and require sufficient students to achieve economies of scale with delivery” (Zhang & Worthington, , p. 1788).…”
Section: Towards Understanding Materiality In Dementioning
confidence: 99%